Intergenerational risk sharing, pensions and endogenous labor supply in general equilibrium - Roel Beetsma; Ward E. Romp; Siert J. Vos (Center for Economic Studies and ifo Institute (CESifo), 2008)
In the context of a two-tier pension system, with a pay-as-you-go first tier and a fully funded second tier, we demonstrate that a system with a defined wage-indexed second tier performs strictly better than one with a defined contribution or defined real benefit second tier. The former completely separates systematic redistribution (confined to the first tier) from intergenerational risk sharing (the role of the second tier). This way labor supply is undistorted.
Keywords: E21; 330; funded pensions; risk sharing; overlapping generations; endogenous labour supply; Generationenbeziehungen; Risikopräferenz; Alterssicherung; Overlapping Generations; Allgemeines Gleichgewicht